126 USE OF A HANDHELD ASSIST DEVICE FOR CHOLESTEROL MANAGEMENT BY NATIONAL CHOLESTEROL EDUCATION PANEL ADULT TREATMENT PANEL III GUIDELINES. (10th December 2015) - Rashid, M.; Goebel, L.; Wehner, P.; Seifu, M.; Gress, T.
Abstract : Purpose: A previous study showed cholesterol guidelines to be inconvenient to use during patient encounters. We assessed the ability of a handheld assist device (HAD) to assist physicians with cholesterol management. Methods: We performed a cohort study using 116 patients with dyslipidemia (ICD-9 codes 272.0-272.9). The HAD group (n = 63) was drawn from the practices of nine interns who were provided with a HAD and instructed on its use to determine the Adult Treatment Panel III recommendation. The non-HAD group (n = 53) was drawn from the practices of ten interns not using a HAD. We reviewed baseline and 6-month follow-up data on each patient to determine the proportion of patients at their target low density lipoprotein cholesterol (LDL-C) and the number of times a physician made a change in management. In addition, we surveyed intern attitudes regarding HAD use. Results: Ninety-two patients (79%) had an LDL-C during the study period. Target LDL-C was achieved in 29 patients (59.2%) in the HAD group and in 24 patients (55.8%) in the non-HAD group (p = .64). Among 39 patients (42.4%) not at target LDL-C, 24 had no change in management (12 per group; p = .71). Self-reported intern guideline use doubled in the HAD group. The interns rated the HAD as excellent for convenience, ease of use, as a tool for lipid management, and as a tool for assessing the Framingham Risk Assessment Score (FRAS). Conclusion: Although providing interns with a HAD was not associated with a short-term improvement in cholesterol management, it may lead to increased use of cholesterol guidelines.